Pengaruh Metode Latihan Whole Body Reaction terhadap Kecepatan Reaksi Kiper Futsal - Hamjah, Amir; Sartono, Sartono (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This study aims to evaluate the effect of the Whole Body Reaction training method on the reaction speed of futsal goalkeepers. The research method used was experimentation with pre-test and post-test. The research sample consisted of 25 futsal goalkeepers who were divided into two groups, namely the control group and the experimental group. The experimental group underwent training using the Whole Body Reaction method, while the control group received no special treatment. The pre-test and post-test results showed changes in reaction speed. Data obtained from the Whole Body Reaction test was processed using a contingency table to analyze the differences between pre-test and post-test results. Keywords: Futsal, Speed, Goalkeeper.